Analisis Faktor-faktor yang Mempengaruhi Pemilihan Metode Kontrasepsi Jangka Panjang (MKIP) pada Wanita Pasangan Usia Subur (PUS) di Kabupaten Kendal Tahun 2013 - Sri Setiasih; Bagoes Widjanarko; Tinuk Istiarti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTAnalysis Factors Affecting Selection Of Long-Term Contraception Method (Ltcm) Non Hormonal On Woman Of Fertile Couple (Pus) In Kendal By 2013; Women of fertile couple more than 30 years old have a higher risk factor for their health, including reproduction, which is expected they will use LTCM non-Hormonal. The purpose of this study is to analyze factors that related to the selection of LTCM Non-Hormonal in women of fertile couple in Kendal 2013. The type of this research is descriptive analytics and cross-sectional design with quantitative and qualitative approaches and the sample is 400 respondents from 20 districts in Kendal Regency. The qualitative sample is 6 respondents. The results showed a relationship between knowledge with selection of contraception method (p value = 0.034), there is a relationship between attitudes to the selection of contraception method (p value = 0.027), there is a relationship between support of birth control officer with selection contraception method (p value = 0.049), and there is a correlation between the availability of service of birth control with the selection of contraception method (p value = 0.011), there is no relationship between husband support to selection of contraception method (p value = 0835, and there is no relationship between religious leaders or community leaders on selection contraception method (p value = 0384). The most influential factor in the selection of LTCM non-hormonal is the attitude with OR 2,041.Keywords : selection of long term contraception, factor, affect